Development of a Board Game-Based Information Service Media to Support Students’ Understanding of Bullying Prevention at SMP IT Al-Hijrah Medan - Sri Nita Yani Sihombing; Purbatua Manurung (Journal of Education and Teaching Learning, 2026)
The goal of this study is to create board game media for information services that will help students at Al Hijrah IT Junior High School in Medan comprehend the risks associated with bullying. The ADDIE development model, which comprises the phases of analysis, design, development, implementation, and evaluation, is used in this study together with the Research and Development (RND) approach. A sample of twenty-five pupils from SMP IT Al Hijrah Medan's seventh-grade student body served as the study's subject. Observation, interviews, and expert validation questionnaires were employed as data gathering methods. The analysis's findings indicated that the information service media used in schools was still basic, necessitating the usage of more engaging and entertaining media. According to the study's findings, the Board Game game media received 90% media expert validation and 93% material expert validation results with a highly valid category. Additionally, the student reaction was 85% with the category of extremely possible and the teacher's response was 87%. When information services on stopping bullying are implemented, the media created is thot to be able to boost student interest, activity, and engagement. Therefore, it is said that the board game media is very appropriate for usage as an information service medium to provide students at Al Hijrah IT Junior High School Medan an awareness of how to combat bullying.